Interventional laser surgery for oral potentially malignant disorders: a longitudinal patient cohort study. Issue 3 (March 2017) - Thomson, P.J.; Goodson, M.L.; Cocks, K.; Turner, J.E.
Abstract: Oral squamous cell carcinoma (OSCC) is a lethal disease, with rising incidence. There were 6767 new OSCC cases and 2056 deaths in the UK in 2011. Cancers are preceded by oral potentially malignant disorders (PMDs), recognizable mucosal diseases harbouring increased SCC risk, offering clinicians a 'therapeutic window' to intervene. Contemporary practice remains unable to predict lesion behaviour or quantify malignant transformation risk. No clear management guidelines exist and it is unclear from the literature whether early diagnosis and intervention prevents cancer. Between 1996 and 2014, 773 laser treatments were performed on 590 PMD patients in Newcastle maxillofacial surgery departments. The efficacy of the intervention was examined by review of the clinicopathological details and clinical outcomes of the patients (mean follow-up 7.3 years). Histopathology required up-grading in 36.1% on examining excision specimens. Seventy-five percent of patients were disease-free, mostly younger patients with low-grade dysplasia; 9% exhibited persistent disease and were generally older with proliferative verrucous leukoplakia. Disease-free status was less likely for erythroleukoplakia ( P = 0.022), 'high-grade' dysplasia ( P < 0.0001), and with lichenoid inflammation ( P = 0.028). Unexpected OSCC was identified in 12.0%, whilst 4.8% transformed to malignancy. Interventional laser surgery facilitates definitive diagnosis and treatment, allows early diagnosis of OSCC, identifies progressive disease, and defines outcome categories. Evidence is lacking that intervention halts carcinogenesis. Multicentre, prospective, randomized controlled trials are needed to confirm the efficacy of surgery.